Diversity of the Ganoderma species in Uruguay - Morera, G. (2021)
Ganoderma is a cosmopolitan genus that includes a great diversity of species. Many of them have been historically described based only on morphological characteristics; however, due to their morphological plasticity, there is no complete understanding about their relationship and taxonomic status. Commonly applied names, particularly in the southern Neotropics, come from species of North Hemisphere distribution (e.g. G. lucidum, G. resinaceum and G. applanatum). The objective of the present work was to perform a survey of Ganoderma species thriving in Uruguay. We aimed to identify and characterize them through molecular, morphological and ecological analysis. The results confirm the presence of four reddish laccate species first registered for Uruguay (G. dorsale, G. platense, G. martinicense and G. mexicanum), and one non-laccate species (G. australe s.l.) composed of two clades. The species are morphologically differentiated mainly by its stipe, pilear surface, context, pores, basidiospores and cutis cells. Regarding the ecological data, the species present differences in substrate preferences. In addition, a taxonomic discussion regarding phylogenetic relationships and taxonomic status of Uruguayan Ganoderma species is presented.